Training on Writing Scientific Papers for Teachers at Public Junior High School 3 Batukliang, Central Lombok - Susilawati Susilawati; Hairunnisyah Sahidu; Aris Doyan; Ahmad Harjono; Hikmawati Hikmawati (Pascasarjana Universitas Mataram, 2023)
This training activity aims to improve the competence of teachers at Public Junior High School 3 Batukliang, Central Lombok Regency in the field of writing scientific papers. This activity is carried out in three stages. The stages involved in solving this problem are the preparation stage, the implementation stage, and the evaluation stage. The results of the training showed that the teachers who attended were very enthusiastic about following and observing what was explained by the community service team regarding the models and strategies taught in class to compile them into a scientific work. In addition, the training participants wanted the training activities to be sustainable.